1997
DOI: 10.1159/000282973
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ageing and X-lrradiation on the Diurnal Rhythm of Mouse Urinary Bladder Capacity

Abstract: The effect of single-dose irradiation (19 Gy) or sham treatment on circadian variations in urinary bladder storage capacity was assessed during a 250-day period following treatment using transurethral cystometry under anesthesia. Changes in bladder function were quantified as the deviation from individual pretreatment values of bladder volume at defined intravesical pressures. A marked diurnal rhythm with a peak at 19.00 h and an extended nadir between 1.00 h and 12.00 h was found in 11- to 12-week-old untreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
0
2
Order By: Relevance
“…Two previous studies of the circadian profile of bladder capacity from anesthetized, chronically-implanted mice differ from the data presented here, showing a lower bladder capacity during the light phase which increases in the early portion of the dark phase [20][21]. Because those animals were anesthetized, it remains to be determined how the phase of the normal voiding cycle compares in rat and mouse bladders.…”
Section: Discussioncontrasting
confidence: 69%
“…Two previous studies of the circadian profile of bladder capacity from anesthetized, chronically-implanted mice differ from the data presented here, showing a lower bladder capacity during the light phase which increases in the early portion of the dark phase [20][21]. Because those animals were anesthetized, it remains to be determined how the phase of the normal voiding cycle compares in rat and mouse bladders.…”
Section: Discussioncontrasting
confidence: 69%
“…This is consistent with prior studies that showed a circadian difference in bladder capacity and micturition frequency in rodents with no surgery 16,17 and chronically catheterized animals. 18,19 We do, however, report a difference in diurnal bladder pressure that has not previously been reported. In fact, Herrera et al, 20 observed no difference in the average bladder pressure between light and dark phases.…”
Section: Discussioncontrasting
confidence: 69%